The Effect on Lactation of Back Massage Performed in the Early Postpartum Period (Journal of Basic and Applied Research in Biomedicine, 2022)
Background & Aim: The mother’s milk is by itself a sufficient food for the growth and development of a newly-born baby. Lactation begins after a woman has given birth, and it is thought that hormones, along with the physiological changes which take place, have an effect on this process. The aim of this study was to examine the levels of oxytocin, prolactin and noradrenalin and levels of the Beck Depression Scale in order to determine the effects on lactation of back massage carried out in the early postpartum period. Methods: We randomly assigned 60 women who had a normal delivery into two groups: a massage group and a controlgroup. TheBeck Depression Questionnaire was applied to the groups, and 2 cc blood samples were taken for measurement ofthe levels of prolactin, oxytocin and noradrenalin by the Elisa method.(Milipore Corporation, Billerica, MA, USA). Results: We observed that levels of noradrenalin fell to a statistically significant extent in the massage group compared with the control group (p